Pursuing Happiness In Eat Pray Love Movie (2010) Directed By Ryan Murphy: A Psychoanalytic Approach - Rutama, Aulia Novika (2012)
The research is proposed to analyze pursuing happiness of Liz Gilbert's personalities in facing her depression with Psychoanalytic Approach. The major problem in this research is how the pursuing happiness is reflected in Eat Pray Love movie. The objective of the tudy is to analyze the film based on its structural element and to analyze the film based on the psychoanalytic approach. This study is a descriptive qualitative study, using the movie of Ryan Murphy's Eat Pray Love. And Eat Pray Love's major character as the object of analysis of the study. There are two kinds of data sources used in this analysis, namely primary and the secondary. The primary data sources are the play and script of the play itself and the secondary data sources are some books, internet and articles related to the subject. The technique of data collection in this research is watching the original movie for several times; reading the movie script; determining the character that will be analyzed; taking notes of important thing both of primary and secondary data sources; classifying and determining the relevant data and; notes the material and other resources related the movie and the analysis. In analyzing the data, the researcher employs descriptive qualitative analysis. For the last, the researcher makes an analysis of Liz Gilbert's id, ego, and superego. The researcher uses the theory of Psychoanalytic by Sigmund Freud because it is relevant to the problem. Based on the analysis, the outcome of this study shows the following conclusion. Firstly, there is a close relationship between a work of literature and Psychoanalysis Phenomena. Secondly, the general conclusion of psychoanalysis of humans is when people get desperate then they pursue the happiness.